2008
DOI: 10.1002/mus.20978
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit recruitment and bursts of activity in the surface electromyogram during a sustained contraction

Abstract: Bursts of activity in the surface electromyogram (EMG) during a sustained contraction have been interpreted as corresponding to the transient recruitment of motor units, but this association has never been confirmed. The current study compared the timing of trains of action potentials discharged by single motor units during a sustained contraction with the bursts of activity detected in the surface EMG signal. The 20 motor units from 6 subjects [recruitment threshold, 35.3 +/- 11.3% maximal voluntary contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
(58 reference statements)
3
25
1
Order By: Relevance
“…These results are consistent with indirect evidence supporting a tendency toward repetitive motor unit discharge in older adults as suggested by the decreased rate of bursts of activity in the surface EMG recordings (Riley et al 2008b) when the elbow flexor muscles supported an inertial load and pulled up against a rigid restraint during fatiguing contractions that were sustained at 20% MVC force (Hunter et al 2005). In contrast to the present findings, young adults varied the CV for ISI but not mean discharge rate across the two target forces with the rigid restraint, but again the old adults modulated neither discharge property across the two target forces (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with indirect evidence supporting a tendency toward repetitive motor unit discharge in older adults as suggested by the decreased rate of bursts of activity in the surface EMG recordings (Riley et al 2008b) when the elbow flexor muscles supported an inertial load and pulled up against a rigid restraint during fatiguing contractions that were sustained at 20% MVC force (Hunter et al 2005). In contrast to the present findings, young adults varied the CV for ISI but not mean discharge rate across the two target forces with the rigid restraint, but again the old adults modulated neither discharge property across the two target forces (Table 2).…”
Section: Discussionsupporting
confidence: 91%
“…Potvin and Brown 44) speculated that this pre-processing would improve the signal quality because the low-frequency component of the original surface EMG signals contains the distorted components due to unwanted low-pass filtering when passing from muscle fibers to electrodes, resulting in signal components unrelated to motor unit action potentials. In line with this notion, Riley and colleagues 45) indicated that high-pass filtering of interference EMG resulted in stronger associations between surface EMG and trains of motor unit action potentials as compared with those obtained from …”
Section: Resultsmentioning
confidence: 84%
“…Compared to traditional filtering (e.g., 10-20 Hz highpass cutoff), whitening and extreme highpass filtering improve muscle sEMG-to-force estimates during rested (Potvin and Brown, 2004;Staudenmann et al, 2007;Riley et al, 2008) and fatiguing contractions (Cort et al, 2006;Potvin et al, 2010;La delfa et al, 2014). Importantly, Cort et al (2006) showed that the ratio between whitened sEMG amplitude and elbow moment was relatively constant during fatiguing isometric elbow flexor contractions.…”
Section: Surface Electromyography and Force Filteringmentioning
confidence: 93%